ผลกระทบของแนวเขื่อนป้องกันน้ำท่วมที่มีต่อชุมชนริมน้ำ : กรณีศึกษาชุมชนปากคลองชักพระ กรุงเทพมหานคร - ศิระษา สัมฤทธิ์ผลเกิด (จุฬาลงกรณ์มหาวิทยาลัย, 2010)
To study the impact of the flood prevention dike with the waterfront community of PAK Khlong Chak Phra area, Bangkok. We want to find out that constructing the flood prevention dike affect whether the physical and social community. There are assumtions that flood prevention dike reduce the level of community access to the water and changes in physical factors that affect the waterfront community’s life. There are research methods (1) studying building mass and space, and the key elements of the waterfront community in the community level and house level by using Geographic Information Systems (GIS) and using Physical Survey in house level of waterfront area and (2) studying social changes with questionnaire and in-depth interviews. Then, the findings are analyzed and related to compare changes before and after constructing the flood prevention dike in the physical and social side. We find the relationship of changing between the two sides with prove changes of physical factors and measuring the social impacts caused by that physical changes. The results are showed that the flood prevention dike affects the people who live in the waterfront community of Pak Khlong Chak Phra get benefits. Flood prevention dikes can alleviate flooding and can reduce the bank erosion. However, the flood prevention dike impacts changing of physical and social changes of the community. (1) Physical changes in the community are found that waterfront area is cut through with the flood prevention dike. The relationships between human and water are blocked. Access to water from the community are decrease that resulting to the need for land transport as the major routes. The lost of buildings mass(pier) in the waterfront area reduces the public areas of house’s groups. The area of activities in the waterfront community are decrease accordingly. The routes in community are important role as the cause of grouping the inter-buildings space and religion building’s area that is the public space for grouping community at the present time. (2) Physical changes in the house level occurred by most to minimum : the opening channel to water(boat parking), the location of the building in water, pier, building orientations, waterfront area and the up-down stair into the water. The physical factor that is increase is the fence. And (3) social changes are due to the changes in the physical elements that mentioned above. Social changes are the rest, the interaction of the community, cultural activities, the travel, the consumption, the career and safety. It is found that the houses that is close to the dike are affected more than the house that is not. Also, it is found that changing of physical elements in the house level is important result that affects social changes consequently. The findings lead to suggestions that the government agency should consider serverance pay for the damage or lost of the physical elements such as the construction of up-down stair to the water in the need area for serving residents that are important to the various activities of waterfront community. Also, the government agency should study the components of flood prevention dike of the state in construction’s purpose or using’s purpose in each area to compare the result of the studies and using for planning the flood prevention dike that is appropriate and applicable to other areas.